Cortical thickness, resting state heart rate, and heart rate variability in female adolescents - Koenig, Julian; Parzer, Peter; Reichl, Corinna; Ando, Ayaka; Brunner, Romuald; Kaess, Michael (Psychophysiology, 2018)
Resting state heart rate variability (HRV) is a psychophysiological marker that has gained increasing research interest, in particular in developmental neuroscience. HRV has been shown to be associated with mental and physical health, beyond simple measures of heart rate (HR) and shows inter- and intraindividual variance across aging. Recently, three studies reported on a positive correlation between resting state HRV and cortical thickness in selected regions of interest (ROIs) in adult samples. Structural thickness, HRV, and HR change during the sensitive period of adolescence. Previously, no study has addressed the structural concomitants of resting HR and HRV in adolescents. Cortical thickness (3-T MRI), HR, and HRV were recorded in 20 healthy, female adolescents (mean age: 15.92 years; SD = 1.06; range: 14-17). In line with existing research in adults, cortical thickness in a number of ROIs was associated with resting state HRV but not HR. The comparison of regression analyses using the Bayes factor revealed evidence for a correlation between HRV and cortical thickness of the bilateral rostral anterior cingulate cortex. However, unlike in adults, greater cortical thickness was associated with reduced HRV in female adolescents. Analyses on HR showed no superior model fit. Results suggest that greater HRV might be beneficial for cortical development during adolescence (cortical thinning). On the other hand, cortical development might determine changes in autonomic nervous system function in adolescents. Future studies are needed to replicate these findings in larger samples including boys and to test these hypotheses in longitudinal designs.